Racism in patient care: a call to translate concerns into actions - Wen Hui Lim; Wilson Sim; Cheng Han Ng; Yip Han Chin; Clyve Leon; Dujeepa D Samarasekera, MHPE; M Kamala Devi, PhD; Chin Meng Khoo; Choon Seng Chong (Elsevier, 2021)
Background: Racial injustices in health care lead to poor health outcomes in minority groups. Such health inequality has been exacerbated in times of COVID-19 which has seen disproportionately high mortality in minority communities. The objective of the study was to better understand the nature of racial bias in clinical settings to inspire changes in the way healthcare providers interact with their patients to improve health outcomes. Methods: We did systematic searches of four electronic databases:, Medline, CINAHL, PsycINFO and Web of Science using the search terms "Exp Racism/ and (Exp Health Personnel/ or Exp Attitude of Health Personnel/) and Exp Qualitative Research/" in the title and abstract to identify articles published in English between Dec 1, 1978, and June 25, 2020. Titles and abstracts were sieved, followed by a full text review. Data synthesis and inductive thematic analysis were conducted using the Thomas and Harden methodology. Findings: We included 23 articles that reported data for 1006 participants aged 24 to 89 years. Included studies were from six countries, mostly the USA (n=15, 65%) and UK (3, 13%). Perspectives from both minority patients and health-care providers were included. Three themes were generated: alienation of minority patients, labelling of minority patients and denial of racism. Alienation of patients resulted from supremacism of healthcare providers who were condescending in their attitudes (11, 48%). Health-care providers were less empathetic, as evident from their cold dispositions and body language (14, 61%). Minority patients reported being subjected to labelling and generalisations about their lower socioeconomic class, lifestyle practices and needs, which led to inadequate treatment such as denial of drug therapy (12, 52%). Providers were also fearful of minorities because of negative assumptions and stereotypes (3, 13%). By contrast, some patients and providers denied the presence of racism in health care. Providers felt that they treated all patients equally (6, 26%). They suggested that minority patients were oversensitive and shifted blame onto lack of patient compliance, rather than racism, for poor health outcomes (6, 26%). Interpretation: Implicit racial bias in patient-provider interactions is pervasive, thus exacerbating health disparities in minorities. Our findings serve as a call to action for health-care institutions to implement targeted anti-racism interventions such as diversity training, anti-racism forums and increased implicit bias education. We may have underestimated the extent of racism in health care since we included only articles published in English, thus missing relevant studies of minorities published in a language other than English. The strength of this article is that it includes perspectives about racism from not only patients from minority groups but also health-care providers. Funding: None.